Determinants of Interest In Using Sharia Peer To Peer Lending In Indonesia - Sumarnah, Riski (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
Background: Many business actors are turning financial service technology, namely financial technology or what is known as fintech, into an innovation to survive in their business. One of the Sharia fintech products is a Sharia peer-to-peer lending service that brings together lenders and borrowers. The presence of peer-to-peer lending will make it easier for people to provide loans or apply for loan funds for various purposes without using the services of financial institutions as intermediaries. Objectives: This research aims to determine whether financial literacy, digital literacy, Perceived Usefulness, Perceived Ease of Use, and subjective norms influence a person's interest in using Sharia peer-to-peer lending. Novelty: This research has differences in case studies, namely: it focuses more on fintech products, namely Sharia peer-to-peer lending. Then include the digital literacy variable because there is not much research that focuses on the influence of digital literacy on interest in using sharia peer-to-peer lending. Research Methodology / Design: This research uses a quantitative approach, with primary data from 180 respondents which is then processed using a partial-least square structural equation modeling (PLS-SEM) approach with the help of the Smart-PLS 4 analysis tool. Findings: The results of this research show that financial literacy and digital literacy do not significantly influence interest in using sharia peer-to-peer lending in Indonesia. Meanwhile, Perceived Usefulness, Perceived Ease of Use, and subjective norms significantly influence interest in using sharia peer-to-peer lending in Indonesia. Implication: It is highly recommended that related companies continue to socialize the security and legality of the new Sharia Peer Peer Lending application to educate the Indonesian people about financial and digital literacy.